Spatial patterns and geographic characteristics of tourism-accommodation intensity hotspots in Kyoto city - Haruka Kato (Annals of Tourism Research Empirical Insights)
The tourism intensity index can be used to determine the risk of overtourism. This study aimed to clarify the spatial patterns and geographic characteristics of tourism-accommodation hotspots in Kyoto City. This study calculated the tourism-accommodation intensity index as the ratio of the number of accommodation rooms to that of households. The results revealed that tourism-accommodation intensity hotspots emerged in neighborhoods near the periphery of the southeastern historical center. The hotspots emerged in neighborhoods where the number of rooms has exceeded that of households. Additionally, this study revealed that tourism-accommodation intensity hotspots were spatially associated with proximity to main stations and world heritage sites. This study's findings are useful for developing effective urban zones with total volume control in these neighborhood-units.